Construction of a Faculty Development Model forApplication-Oriented Undergraduate Universities inChina Based on Educational Ecology Theory (Foro de Educacion, 2025)
In the context of application-oriented undergraduate universities in China, faculty development programs are often generic and fail to address the specific needs of educators in application-orientated disciplines. The purpose of this study is to analyse the practices, challenges, and ecological aspects that influence the professional growth of faculty in universities. This study aims to elaborate on a faculty development model based on Educational Ecology Theory by incorporating multiple sources that influence the faculty’s development process. The qualitative research design was used, and the primary data collection method was semi-structured interviews. Purposefully, 23 participants were selected, including faculty members, administrators from application-oriented undergraduate universities in China, and representatives of partner enterprises. Thematic analysis of the data leads to themes concerning the strengths and weaknesses of current development programmes and challenges faced, as well as the effect ecological factors had on faculty development. Current faculty development programmes are disengaged from the needs of current application-oriented disciplines, as shown by the study. There were time constraints, limited resources, and no tailored professional development. In addition, institutional policies, inflexible curricula, and resource constraints restrict the development of novel teaching practices. A context-specific, industry-relevant faculty development programme that integrates ecological factors is emphasised by the findings. Faculty in application-oriented disciplines must be well supported through flexible and tailored professional development opportunities, which should be backed by policymakers and universities.